(742) دراسات فى المجتمع الريفى فى الجمهورية العربية المتحدة - همام، عز الدين (معهد التخطيط القومى, 2026)
ab يتناول هذا العمل دراسة تحليلية للمجتمع الريفي في الجمهورية العربية المتحدة، من منظور اجتماعي واقتصادي وإداري. ويهدف إلى فهم الخصائص الأساسية للمجتمع الريفي والعوامل المؤثرة في تطوره، مع التركيز على العلاقة المتبادلة بين السكان والموارد الاقتصادية، وبنية التنظيم الاجتماعي والإداري في الريف.تبدأ الدراسة بتحليل البعد السكاني، موضحة أن النمو السكاني يمثل عاملاً حاسماً في تشكيل الأوضاع الاقتصادية والاجتماعية. وتناقش العلاقة بين زيادة عدد السكان وتوافر الموارد الزراعية، مبينة أن اختلال التوازن بينهما قد يؤدي إلى انخفاض نصيب الفرد من الموارد والإنتاج، وما يترتب على ذلك من تراجع مستوى المعيشة وظهور مشكلات اقتصادية واجتماعية متعددة. كما تستعرض الدراسة بيانات ومؤشرات إحصائية توضح تطور السكان والأراضي الزراعية، وتبرز أثر النمو السكاني المتسارع على التنمية الريفية.وتنتقل الدراسة إلى تحليل البناء الاجتماعي للريف، فتتناول طبيعة العلاقات الاجتماعية السائدة، وأنماط القيادة المحلية، ودور المؤسسات التقليدية في إدارة شؤون المجتمع. كما تبحث في التنظيم الإداري المحلي، بما في ذلك نظام العُمد والمشايخ، ودوره في الربط بين الدولة والسكان الريفيين، مع مناقشة المزايا والقيود المرتبطة بهذا النظام من حيث الكفاءة الإدارية والرقابة وتحقيق المصالح المحلية.وتبرز الدراسة أهمية فهم الخصائص السكانية والاجتماعية للمجتمعات الريفية عند وضع السياسات التنموية، مؤكدة أن التنمية الفعالة تتطلب التوفيق بين النمو السكاني والموارد المتاحة، وتحسين الهياكل الإدارية والمؤسسات المحلية. كما تشير إلى أن المشكلات الريفية ليست اقتصادية فحسب، بل ترتبط أيضاً بعوامل اجتماعية وتنظيمية وثقافية تؤثر في عملية التغيير والتنمية.وتخلص الدراسة إلى أن تطوير المجتمع الريفي يستلزم تبني رؤية متكاملة تجمع بين التخطيط الاقتصادي، وتنمية الموارد الزراعية، وتحسين الإدارة المحلية، وتعزيز المشاركة المجتمعية، بما يضمن رفع مستوى المعيشة وتحقيق تنمية ريفية أكثر استدامة. This study provides a comprehensive analytical examination of rural society in the United Arab Republic from social, economic, demographic, and administrative perspectives. The work seeks to identify the fundamental characteristics of rural communities and to explain the factors shaping their development, with particular emphasis on the interaction between population growth, economic resources, and local institutional structures. A major component of the study focuses on demographic analysis. The author argues that population growth is a critical determinant of social and economic conditions in rural areas. By examining statistical indicators related to population expansion and agricultural land resources, the study highlights the challenges created when population growth exceeds the rate of resource development. Such imbalance may reduce per capita access to productive resources, lower living standards, and generate a range of economic and social pressures within rural communities. The study also investigates the social structure of rural society. It explores patterns of social relations, community leadership, and traditional forms of local authority. Particular attention is given to the administrative organization of villages, including the roles of village headmen and local notables in linking rural populations with governmental institutions. The author evaluates both the strengths and weaknesses of these arrangements, discussing issues of administrative effectiveness, accountability, and local representation. Beyond demographic and administrative dimensions, the work emphasizes the interconnected nature of rural development. It argues that economic progress cannot be understood independently from social organization, cultural traditions, and institutional frameworks. Rural problems are therefore presented as multidimensional phenomena requiring integrated solutions rather than purely economic interventions.The study concludes that sustainable rural development depends on achieving a balance between population growth and available resources, while simultaneously strengthening local administration and community institutions. Effective planning, agricultural development, improved governance, and greater participation by rural residents are identified as essential elements for enhancing living standards and promoting long-term social and economic progress. The work remains a valuable contribution to understanding the dynamics of rural society and the challenges of development in agrarian communities.